Climate change impacts on coffee production in Indonesia: A review - Ramadhillah, Balqis; Masjud, Yunita Ismail (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Indonesia is ranked in the top 5 coffee production countries in the world with the largest production being Arabica and Robusta coffee beans. Approximately ninety percent of coffee produced in Indonesia is being exported and as the trend in local consumption increases, the demand for coffee is escalating. However, future coffee production is challenged by climate change. Background: This paper outlines the impacts of climate change variables including environmental stressors on coffee production quality and quantity of Arabica and Robusta species, discusses the influences on suitable areas for coffee cultivation and the coffee pests related to coffee productivity, as well as suggests mitigation and adaptation approaches in Indonesia. Methods: The literature review approach was utilized to complete this paper which involves collecting, analyzing, and correlating the findings of prior studies. The paper only considered literature with the following terms in the title; climate change impact, coffee production, mitigation, adaptation, and Indonesia. Finding: Increasing temperature degrades coffee production both in Arabica and Robusta coffee beans. The overall suitable area for cultivating coffee is shifting towards higher altitudes However, Indonesia is projected to lose more than half of the suitable area for cultivating Arabica by the year 2050. Climate change improves coffee pests' thermal tolerance and enables them to grow in warm temperatures. Conclusion: Common mitigation approaches include shade plantation and soil moisturization control which both improve coffee productivity. Another strategy is the cultivation calendar modified the coffee life cycle with climate prediction.